ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG CINDERAMATA(STUDI KASUS CINDERAMATA KHAS PAPUA KHUSUSNYA DAERAH TIMIKA) - Michael Maldini Suak; Rosdiana (CV. Adiba Aisha Amira, 2023)
This study aims to determine the factors that influence the income of typical Papuan souvenir traders in Timika City. The research method used is associative, which is a type of research that aims to determine the relationship between two or more variables. The associative research method was used in this study to determine the effect of local wisdom, product uniqueness, spiritual values, and historical values on the income of typical Papuan souvenir traders in Timika City. In this study the data collection techniques used were questionnaires and interviews. To find out these factors, the analysis used in this study is Multiple Linear Regression analysis. The results of the study of two of the four factors show that there is an influence on the income of typical Papuan souvenir traders in Timika City, these factors include Local Wisdom (X1), Product Uniqueness (X2), Spiritual Value (X3) and Historical/Historical Value (X4) simultaneously influencing positive and significant to the income of typical Papuan souvenir traders in Timika City.